2016
DOI: 10.1159/000448347
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Accuracy of Thermography and Mammography in the Detection of Breast Cancer

Abstract: Background: Benefits and harms of screening mammography have been disputed in recent years. This fact, along with the limitations of mammography as well as its unavailability in all our medical centers, tempted us to evaluate the accuracy of thermography in detecting breast abnormalities. Patients and Methods: All patients who were candidates for breast biopsy were examined by both mammography and thermography before tissue sampling in a referral center between January 2013 and January 2014. We defined sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…The higher the temperature, the more heat is being emitted by the object. Thermography has long been used for the detection of breast cancer by measuring the surface temperature of the breast . It is based on the idea that the temperature of lumps of cells is higher than surrounding normal tissue due to an increase in blood circulation in the former.…”
Section: Introductionmentioning
confidence: 52%
“…The higher the temperature, the more heat is being emitted by the object. Thermography has long been used for the detection of breast cancer by measuring the surface temperature of the breast . It is based on the idea that the temperature of lumps of cells is higher than surrounding normal tissue due to an increase in blood circulation in the former.…”
Section: Introductionmentioning
confidence: 52%
“…In addition, Omranipour et al (2016[27]) compared the sensitivity and specificity of mammography with thermography (80.5 %, 73.3 % and 81.6 %, 57.8 % respectively). In a similar study Prasad et al (2016[30]) found that breast malignancy was accurately detected in 60 patients (92.31 %) using thermography and 62 out of 65 patients (95.38 %) using MMG.…”
Section: Discussionmentioning
confidence: 99%
“…Jak dotąd wiele prób wykorzystania kamery termowizyjnej w medycynie dotyczyło diagnostyki raka piersi. W piśmiennictwie można znaleźć dane wskazujące, iż termografia może być pomocna do wyznaczenia granicy pomiędzy obszarem tkanki zdrowej a zajętym procesem nowotworowym [6,7,8]. We wszystkich przypadkach podkreślana jest jednak konieczność uzupełnienia diagnostyki i wykonania badań specjalistycznych, tj.…”
Section: Zastosowanie Termografii W Medycynieunclassified